Sharia Marketing Strategy in Attracting the Interest of Students of SD Muhammadiyah Satu Sedati, Sidoarjo: Strategi Pemasaran Syariah Dalam Menarik Minat Peserta Didik SD Muhammadiyah Satu Sedati, Sidoarjo - Kusuma, Angga Dwi Kurniawan; Nurdyansyah, Nurdyansyah; Fahyuni, Eni Fariyatul (Proceedings of The ICECRS, 2020)
The journal entitled "Sharia Marketing Strategies in Attracting the Interest of Students of Muhammadiyah One Sedati Elementary School, Sidoarjo" is one of the results of qualitative research aimed at explaining sharia marketing strategies carried out by Islamic educational institutions of SD Muhammadiyah Satu Sedati. Using descriptive qualitative research methods. Interviews with School Principals and PPDB committee heads, field observations and documentation as a means of data collection techniques. Data reduction analysis was used by researchers in the results of the study over a period of two months. Researchers found the results that some Sharia Marketing Strategies in Attracting Interests of Muhammadiyah One Sedati Elementary School Students, Sidoarjo, namely: 1. characteristics and principles of sharia marketing include: a) Theitis (Rabbaniyah) prioritizes the value of Islamic religion, b) Ethical (Akhlaqiyah) maintaining services and behavior, c) Realistic (Al-Waqi-i'yyah) being flexible and professional and, d) Humanistic (Insaniyyah) social care. 2. Syariah Marketing Strategy which includes: a) segmenting, b) targeting, c) positioning and 3. Syariah Marketing Tactic which includes marketing mix.